КОРЕКЦІЯ ПОХИБОК ВИМІРЮВАЛЬНИХ КАНАЛІВ СТРУМУ В ЗАСОБАХ МОНІТОРИНГУ НОРМАЛЬНОГО РЕЖИМУ ЕНЕРГОСИСТЕМИ - Варський, Г.М.; Сопель, М.Ф.; Танкевич, Е.М.; Яковлева, І.В. (Інститут електродинаміки НАН України, Київ, 2014)
Reasonability of correction of errors of the measuring channels of current with the purpose of increase of accuracy of current vectors monitoring has been validated. The position of the correction module in the structure of measuring channel of monitoring tool and its basic functions have been determined. Importance of the permanent automatic measuring of the second loading of current transformer has been proved. Taking into account possibility of information on individual metrological descriptions of transformer or its parameters accessing, variants of input information and methods of correction have been determined. Experimental test of the offered engineering solutions has been proved their efficiency. References 3, figures 2.